A combined agent for refining reforming-generated oil and its preparation method and application
Patent Information
- Application Number
- CN202211229931.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-09
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-10-09
AI Technical Summary
随着分子筛催化剂的寿命延长,白土吸附胶质的容量有限,而催化剂易吸附胶质在脱烯烃催化剂活性中心上,从而大幅降低催化剂的脱烯烃效率,催化剂寿命也将显著降低
[0047]本发明提供的新型重整生成油精制组合剂,包括第一精制剂和第二精制剂,其中第一精制剂包括MAl混合金属氧化物和粘结剂,第二精制剂为分子筛催化剂或白土。通过两者的灵活组合,即可以在一个或多个反应器内组合使用,根据原料的特点进行优化组合,在处理高杂质含量原料的同时,保证催化剂的有效利用,降低运行成本。
Abstract
Description
Technical Field
[0001] This invention relates to the field of aromatics production, and more specifically, to a refining compound for deep removal of olefins and trace impurities from reformed oil during aromatics production, its preparation method, and its application. Background Technology
[0002] The production process of para-xylene (PX) involves naphtha reforming, disproportionation and alkyl transfer, and isomerization to generate a mixture of C8 aromatic hydrocarbons, the target product. This mixture is then separated by adsorption to obtain the PX product. The reforming product contains the most removed compounds and undergoes further processing before entering the downstream xylene tower. C8 aromatic hydrocarbons are separated at the top of the tower, while the bottom product is converted into the target C8 aromatic hydrocarbon product through disproportionation and alkyl transfer. The C8 aromatic hydrocarbons separated at the top of the tower have high requirements; they must not only remove olefins but also be free of impurities such as S, N, and Cl.
[0003] Olefins, impurities, and gums in reformed C8 aromatics and above products affect downstream adsorbents, equipment, and pipelines, requiring thorough removal. Currently, industrially, hydrogenation and liquid-phase alkylation reactions are used to remove olefins from reformed aromatics. For gum impurities, clay adsorption is conventionally used. However, as the lifespan of molecular sieve catalysts increases, the adsorption capacity of clay for gums becomes limited, and the catalyst readily adsorbs gums onto the active sites of the deolefin removal catalyst, significantly reducing the catalyst's deolefin removal efficiency and lifespan. Furthermore, during the reforming process, chlorinated organic compounds are added to ensure the aromatization reaction. Under abnormal operating conditions, this can cause a sharp increase in the olefin content of the reformed oil or an increase in gum content, leading to deactivation of the deolefin removal clay or molecular sieve catalyst, thus affecting the quality of the mixed C8 aromatics. Even trace amounts can impact product quality.
[0004] CN107760362A uses activated carbon and element-modified molecular sieves with hydroxides as alkaline agents to remove colloids, but it cannot be regenerated, resulting in a significant amount of hazardous waste. Similarly, CN107760358A uses methods such as bleaching clay and activated carbon to remove colloids, but it cannot remove impurities containing chlorine or other substances. The above-mentioned refining agents have some effect on removing colloids, but their effectiveness is limited by the performance of the removing agents and needs further improvement.
[0005] CN105080619A uses molecular sieve protectants containing Ca, Zn, Mg, Fe, B, Na, and K elements to treat colloids. The molecular sieves used include one or more of mordenite, Y-zeolite, clinoptilolite, ZSM-5 molecular sieve, MCM-22, MCM-56, and β-zeolite. Its degumming effect is poor, mainly because the colloids are polycyclic aromatic hydrocarbons with large molecular diameters, making it difficult for the zeolites used to adsorb into the pores, resulting in low efficiency and failing to meet the requirements for long-term industrial operation.
[0006] In the current process of producing paraxylene, the non-hydrogenated refining of reformed oil requires deep removal of olefin impurities and harmful impurities such as gums, sulfur, nitrogen, and chlorine to meet the requirements of adsorption separation of the mixed C8 aromatics in the feed and the operation and safety of downstream towers, exchangers, and heating equipment. However, current refining agents, such as bleaching clay, modified bleaching clay, and molecular sieve catalysts, as well as the processes they commonly employ, cannot effectively remove the aforementioned impurities, resulting in substandard product quality and jeopardizing the safety of downstream equipment. Summary of the Invention
[0007] To address the limitations of existing non-hydrogenated refining processes for reformed oils, which cannot simultaneously and effectively remove olefin impurities, gums, and harmful impurities such as sulfur, nitrogen, and chlorine, this invention provides a novel refining compound for reformed oils, its preparation method, and its applications. Using this refining compound, deep impurity removal can be achieved, effectively protecting the quality of downstream products and ensuring the safe operation of equipment and processes. Furthermore, the produced mixed xylene product exhibits stable quality, overcoming the current challenges of product and equipment instability in production.
[0008] The first aspect of the present invention provides a reforming oil refining compound, comprising a first refining agent and a second refining agent, wherein the first refining agent comprises a mixed metal oxide (MA1) and a binder, and the second refining agent is a molecular sieve catalyst or clay.
[0009] Furthermore, in the MAl mixed metal oxide, M is selected from one or more of Zn, Fe, Ga, Sn, La, and Ce, preferably one or more of La, Zn, and Fe. The M / Al molar ratio in the mixed metal oxide is 0.5–5.0.
[0010] Furthermore, the binder is selected from at least one of alumina and silicon dioxide.
[0011] Furthermore, in the first refining agent, based on the weight of the first refining agent, the content of MA1 mixed metal oxide is 30-95 parts, preferably 40-85 parts; the content of binder is 5-70 parts, preferably 15-60 parts.
[0012] Further, the molecular sieve is selected from at least one of USY, β, MCM-22, MCM-56, AlPO4-5, SAPO-5, SAPO-37, and SAPO-40 molecular sieves; preferably, the molecular sieve is selected from at least one of USY, β, MCM-56, MCM-22, and SAPO-40. The SiO2 / Al2O3 molar ratio of the molecular sieve is 2 to 60.
[0013] Furthermore, the molecular sieve catalyst contains a binder component, which is selected from at least one of silica and alumina. Based on the weight of the molecular sieve catalyst, the binder component content is 20–90 parts.
[0014] Furthermore, the bleaching clay is at least one of modified bleaching clay, activated bleaching clay, and acidic bleaching clay.
[0015] Furthermore, the mass ratio of the first refining agent to the second refining agent is 0.1 to 10.0.
[0016] Furthermore, the method for preparing the first refined preparation includes the following steps:
[0017] (1) Dissolve aluminum salt and metal M salt in water to prepare mixed solution I;
[0018] (2) The alkali metal solution and the mixed solution I obtained in step (1) are mixed and reacted, and the pH of the solution is maintained at 9-11 to obtain a mixed metal hydroxide layered material (MA1). X (OH) Y ;
[0019] (3) Add the polyol to the mixed metal hydroxide layered material obtained in step (2) for layering treatment, and dry to obtain an intermediate;
[0020] (4) The intermediate obtained in step (3) is mixed with the binder precursor, kneaded and calcined to obtain the first refined preparation.
[0021] Furthermore, the aluminum salt mentioned in step (1) is selected from one or more of aluminum nitrate, aluminum sulfate, aluminum chloride, and sodium aluminate.
[0022] Further, the metal M salt mentioned in step (1) is selected from one or more of soluble nitrates, sulfates, halides, and halates. The metal M is selected from one or more of Zn, Fe, Ga, Sn, La, and Ce, preferably one or more of La, Zn, and Fe.
[0023] Furthermore, in step (1), the M / Al molar ratio in the mixed solution I is 0.5 to 5.0.
[0024] Further, in step (2), the alkali metal solution is a carbonate and / or hydroxide. The mass fraction of the solute in the alkali metal solution is 0.01% to 30%.
[0025] Furthermore, the reaction conditions in step (2) are as follows: the reaction temperature is 50 to 200°C and the reaction time is 1 to 100 hours.
[0026] Furthermore, after the reaction in step (2) is completed, the mixture is filtered, washed, and dried in a conventional manner to obtain a mixed metal hydroxide layered material (MA1). X (OH) Y The washing process can be performed using deionized water until neutral. The drying conditions are 30–380°C for 0.5–100 hours.
[0027] Further, the polyol mentioned in step (3) is selected from at least one of polyethylene glycol or polyvinyl alcohol. The polyethylene glycol has a molecular weight of 400 to 10,000, preferably 400 to 8,000, and the polyvinyl alcohol has a molecular weight of less than 130,000, preferably 10,000 to 80,000. The mass percentage concentration of the polyol is 0.1% to 20%.
[0028] Furthermore, in step (3), the mass ratio of the mixed metal hydroxide layered material to the polyol is 0.05 to 2.0.
[0029] Furthermore, the stratification conditions described in step (3) are as follows: temperature is 20-120℃, and time is 0.2-48 hours.
[0030] Further, after the stratification process in step (3) is completed, the intermediate is obtained through conventional filtration, washing, and drying. The washing can be done with deionized water until neutral. The drying conditions are 30–180°C for 2–48 hours.
[0031] Further, the binder precursor mentioned in step (4) is one or more of an alumina precursor (such as boehmite) or a silica precursor (such as silica sol). The amount of the binder precursor added is 10% to 70% of the mass of the intermediate, based on alumina or silica.
[0032] Furthermore, conventional molding aids, such as extrusion aids, lubricants, and pore-forming agents, can be added during step (4) molding. These can be selected from one or more of guar gum powder and cellulose. Drying and calcining after molding is a method familiar to those skilled in the art. Typical drying conditions after catalyst molding are as follows: 50–380℃, drying time 0.5–100 hours; calcination conditions are as follows: calcination temperature 300–700℃, calcination time 0.5–18 hours.
[0033] A second aspect of the present invention provides a method for refining reformed oil, comprising: contacting reactants with the above-mentioned reformed oil refining combination to obtain refined reformed oil.
[0034] Furthermore, the reaction raw materials first pass through a first refining agent to remove impurities such as gum and particles from the reformed oil, as well as a certain amount of olefin impurities, and then pass through a second refining agent to further remove olefin impurities.
[0035] Furthermore, the reactants are products generated from reforming or products obtained from other processes, such as aromatics from cracked hydrogenated gasoline. The olefin content in the reactants, calculated by the bromine index, is 300–2800 mgBr / 100g, and the mass content of the washed gum is 1–60 mg / 100mL.
[0036] Furthermore, the mass ratio of the first refining agent to the second refining agent is 0.1 to 10.0.
[0037] Furthermore, the first and second refining agents can be in one or more containers.
[0038] Furthermore, the reaction raw materials and the above-mentioned reforming oil refining compound are reacted under non-hydrogen-exposed conditions. The reaction conditions for the first refining compound are as follows: reaction temperature 130–350℃, reaction pressure 0.5–4.0 MPa, and liquid hourly space velocity 0.5–20 h⁻¹. -1 The contact reaction conditions for the second refining agent are: liquid hourly space velocity (LHSV) of 0.1–20 h⁻¹. -1 The reaction temperature is 120–280℃, and the reaction pressure is 0.2–5.0 MPa.
[0039] Furthermore, the reforming oil refining agent comprises a first refining agent and a second refining agent, wherein the first refining agent comprises a mixed metal oxide (MA1) and a binder, and the second refining agent is a molecular sieve catalyst or clay.
[0040] Furthermore, in the MAl mixed metal oxide, M is selected from one or more of Zn, Fe, Ga, Sn, La, and Ce, preferably one or more of La, Zn, and Fe. The M / Al molar ratio in the mixed metal oxide is 0.5–5.0.
[0041] Furthermore, the binder is selected from at least one of alumina and silicon dioxide.
[0042] Furthermore, in the first refining agent, based on the weight of the first refining agent, the content of MA1 mixed metal oxide is 30-95 parts, preferably 40-85 parts; the content of binder is 5-70 parts, preferably 15-60 parts.
[0043] Further, the molecular sieve is selected from at least one of USY, β, MCM-22, MCM-56, AlPO4-5, SAPO-5, SAPO-37, and SAPO-40 molecular sieves; preferably, the molecular sieve is selected from at least one of USY, β, MCM-56, MCM-22, and SAPO-40. The SiO2 / Al2O3 molar ratio of the molecular sieve is 2 to 60.
[0044] Furthermore, the molecular sieve catalyst also contains a binder component selected from at least one of silica and alumina. The binder component content is 30–90 parts per unit weight of the molecular sieve catalyst.
[0045] Furthermore, the bleaching clay is at least one of modified bleaching clay, activated bleaching clay, and granular bleaching clay.
[0046] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0047] The novel reforming oil refining compound provided by this invention includes a first refining agent and a second refining agent. The first refining agent comprises a mixed metal oxide (MA1) and a binder, while the second refining agent is a molecular sieve catalyst or clay. Through flexible combination, these two agents can be used in one or more reactors, with optimized combinations based on the characteristics of the feedstock. This allows for the effective utilization of the catalyst while processing feedstocks with high impurity content, thereby reducing operating costs.
[0048] This invention involves the layering and peeling of mixed metal-layered inorganic materials, followed by molding and calcination with a binder to obtain a first refining agent. This agent is then used in combination with a second refining agent, a molecular sieve catalyst, or kaolin to achieve deep impurity removal. This effectively protects the quality of downstream products and the safe operation of equipment processes, overcoming the current problems of product and equipment instability in production. It can be used for large-scale production. Detailed Implementation
[0049] The technical solution of the present invention will be further described below with reference to specific embodiments.
[0050] Example 1
[0051] (1) Weigh 47.0g of aluminum nitrate and 85.2g of zinc nitrate (Zn / Al molar ratio 2) and dissolve them in 750g of water. Mix them thoroughly to obtain mixed solution I.
[0052] (2) A 15% sodium carbonate aqueous solution (containing a small amount of sodium hydroxide solution with a concentration of 0.50 mol / L) was added dropwise to mixed solution I, maintaining the pH of the solution at 9.5, and then reacted at 75°C for 36 hours; then filtered and washed, and dried at 60°C for 24 hours to obtain a mixed metal hydroxide layered material;
[0053] (3) Then take out 15g of the mixed metal hydroxide layered material obtained in step (2), add 500g of polyethylene glycol solution with a molecular weight of 400-1000 (the concentration of polyethylene glycol solution is 2%), treat at 60°C for 8 hours, then filter and wash, and dry at 70°C for 18 hours to obtain the intermediate.
[0054] (4) Take the intermediate obtained in step (3), add 15g of alumina monohydrate and 2g of guar gum powder, then knead and extrude into strips, dry at 120°C for 12 hours, and calcine at 550°C for 3 hours to obtain the first refined preparation, wherein the amount of binder added is 30% of the mass of the intermediate based on alumina.
[0055] In the first refined preparation obtained in Example 1, based on the weight of the first refined preparation, the content of ZnAl mixed metal oxide is 70.1 parts and the content of binder is 29.9 parts.
[0056] Take 5g of the first refining agent and 30g of the second refining agent (containing 70 parts of USY molecular sieve and 30 parts of alumina, with a SiO2 / Al2O3 molar ratio of 5) for evaluation. The raw material is reformed oil with an olefin content of 1220mgBr / 100g and a washed gum content of 10mg / 100mL. The oil is reacted sequentially with both the first and second refining agents, and the reaction time is within 2 hours. -1 (Liquid hourly space velocity during reaction with the first refining agent) and 12h -1 (Liquid hourly space velocity during reaction with the second refining agent), after 100 hours of reaction at 179℃ and 3.0MPa, the olefin content in the reformed oil was 50mgBr / 100g, and the gum content after washing was 3mg / 100mL.
[0057] Example 2
[0058] (1) Weigh 47.0g of aluminum nitrate, 107.6g of lanthanum nitrate, and 21.3g of zinc nitrate (Zn / Al molar ratio 0.5, La / Al molar ratio 1.5) and dissolve them in 750g of water. Mix them thoroughly to obtain mixed solution I.
[0059] (2) Add 15% sodium carbonate aqueous solution (containing a small amount of sodium hydroxide solution with a concentration of 0.9 mol / L) dropwise to mixed solution I, maintain the pH of the solution at 10, and then react at 90°C for 42 hours; then filter and wash, and dry at 90°C for 24 hours to obtain mixed metal hydroxide layered material;
[0060] (3) Then take out 15g of the mixed metal hydroxide layered material obtained in step (2), add 500g of polyethylene glycol solution with a molecular weight of 1000-2000 (the concentration of polyethylene glycol solution is 2%), treat at 90°C for 6 hours, then filter and wash, and dry at 90°C for 18 hours to obtain the intermediate.
[0061] (4) Take the intermediate obtained in step (3), add 8g of alumina monohydrate and 2g of guar gum powder, then knead and extrude into strips, dry at 120°C for 12 hours, and calcine at 550°C for 3 hours to obtain the first refined preparation, wherein the amount of binder added is 20% of the mass of the intermediate based on alumina.
[0062] In the first refined preparation obtained in Example 2, based on the weight of the first refined preparation, the content of the mixed metal oxide of ZnAl and LaAl was 79.7 parts, and the content of the binder was 20.3 parts.
[0063] Take 5g of the first refined product and 20g of the second refined product (containing 75 parts of USY molecular sieve and 25 parts of alumina, with a SiO2 / Al2O3 molar ratio of 6 for USY molecular sieve) for evaluation. The raw material is reformed oil with an olefin content of 1720mgBr / 100g and a post-wash gum content of 50mg / 100mL. The reaction was carried out over 2 hours. -1 and 8h -1 After reacting at 179℃ and 3.0MPa for 100 hours, the olefin content in the reformed oil was 60mgBr / 100g, and the gum content after washing was 6mg / 100mL.
[0064] Example 3
[0065] (1) Weigh 47.0g of aluminum nitrate and 213.6g of ferric nitrate (Fe / Al molar ratio 4) and dissolve them in 750g of water. Mix them thoroughly to obtain mixed solution I.
[0066] (2) A 10% sodium carbonate aqueous solution (containing a small amount of sodium hydroxide solution with a concentration of 0.3 mol / L) was added dropwise to mixed solution I, the pH of the solution was maintained at 9, and then the reaction was carried out at 60°C for 96 hours; then the mixture was filtered and washed, and dried at 40°C for 100 hours to obtain a mixed metal hydroxide layered material.
[0067] (3) Then take out 15g of the mixed metal hydroxide layered material obtained in step (2), add 500g of polyethylene glycol solution with a molecular weight of 4000-8000 (the concentration of polyethylene glycol solution is 6%), treat at 70°C for 12 hours, then filter and wash, and dry at 90°C for 18 hours to obtain the intermediate.
[0068] (4) Take the intermediate obtained in step (3), add 10g of alumina monohydrate and 2g of guar gum powder, then knead and extrude into strips, dry at 90°C for 24 hours, and calcine at 550°C for 3 hours to obtain the first refined preparation, wherein the amount of binder added is 40% of the mass of the intermediate based on alumina.
[0069] In the first refined preparation obtained in Example 3, based on the weight of the first refined preparation, the content of FeAl mixed metal oxide is 59.8 parts and the content of binder is 40.2 parts.
[0070] Take 5g of the first refined product and 20g of the second refined product (containing 80 parts of USY molecular sieve and 20 parts of alumina, with a SiO2 / Al2O3 molar ratio of 4.5 for USY molecular sieve) for evaluation. The raw material is reformed oil with an olefin content of 1220mgBr / 100g and a post-wash gum content of 10mg / 100mL. The reaction was carried out over 2 hours. -1 and 8h -1 After reacting at 179℃ and 3.0MPa for 100 hours, the olefin content in the reformed oil was 65mgBr / 100g, and the gum content after washing was 3mg / 100mL.
[0071] Example 4
[0072] (1) Weigh 47.0g of aluminum nitrate and 32.7g of magnesium nitrate (Mg / Al molar ratio 1) and dissolve them in 750g of water. Mix them thoroughly to obtain mixed solution I.
[0073] (2) Add 8% sodium carbonate aqueous solution (containing a small amount of sodium hydroxide solution with a concentration of 0.2 mol / L) dropwise to mixed solution I, maintain the pH of the solution at 9.5, and then react at 60°C for 96 hours; then filter and wash, and dry at 80°C for 48 hours to obtain mixed metal hydroxide layered material;
[0074] (3) Then take out 20g of the mixed metal hydroxide layered material obtained in step (2), add 600g of polyethylene glycol solution with a molecular weight of 4000-8000 (the concentration of polyethylene glycol solution is 15%), treat at 90°C for 40 hours, then filter and wash, and dry at 90°C for 18 hours to obtain the intermediate.
[0075] (4) Take the intermediate obtained in step (3), add 16g of alumina monohydrate and 2g of guar gum powder, then knead and extrude into strips, dry at 90°C for 24 hours, and calcine at 550°C for 3 hours to obtain the first refined preparation, wherein the amount of binder added is 40% of the mass of the intermediate based on alumina.
[0076] In the first refined preparation obtained in Example 4, based on the weight of the first refined preparation, the content of MgAl mixed metal oxide is 60.2 parts and the content of binder is 39.8 parts.
[0077] Take 5g of the first refining agent and 10g of the second refining agent (containing 80 parts of β-molecular sieve and 20 parts of alumina, with a SiO2 / Al2O3 molar ratio of 22 for β-molecular sieve) for evaluation. The raw material is reformed oil with an olefin content of 1220mgBr / 100g and a post-wash gum content of 16mg / 100mL. The reaction was carried out over 5.0 hours. -1 and 10h -1 After reacting at 179℃ and 3.0MPa for 100 hours, the olefin content in the reformed oil was 65mgBr / 100g, and the gum content after washing was 3mg / 100mL.
[0078] Example 5
[0079] (1) Weigh 47.0g of aluminum nitrate and 166.8g of zinc nitrate (Zn / Al molar ratio 4) and dissolve them in 500g of water. Mix them thoroughly to obtain mixed solution I.
[0080] (2) A 10% sodium carbonate aqueous solution (containing a small amount of sodium hydroxide solution with a concentration of 0.6 mol / L) was added dropwise to mixed solution I, maintaining the pH of the solution at 10.5, and then reacted at 60°C for 96 hours; then filtered and washed, and dried at 100°C for 8 hours to obtain a mixed metal hydroxide layered material;
[0081] (3) Then take out 10g of the mixed metal hydroxide layered material obtained in step (2), add 600g of polyethylene glycol solution with a molecular weight of 3000-8000 (the concentration of polyethylene glycol solution is 10%), treat at 95°C for 7 hours, then filter and wash, and dry at 90°C for 15 hours to obtain the intermediate.
[0082] (4) Take the intermediate obtained in step (3), add 8g of alumina monohydrate and 2g of guar gum powder, then knead and extrude into strips, dry at 120°C for 18 hours, and calcine at 570°C for 2 hours to obtain the first refined preparation, wherein the amount of binder added is 15% of the mass of the intermediate based on alumina.
[0083] In the first refined preparation obtained in Example 5, based on the weight of the first refined preparation, the content of ZnAl mixed metal oxide is 85.8 parts and the content of binder is 14.2 parts.
[0084] Eight g of the first refining agent was mixed with 15 g of the second refining agent (containing 80 parts of USY molecular sieve and 20 parts of alumina, with a SiO2 / Al2O3 molar ratio of 6) for evaluation. The raw material was reformed oil with an olefin content of 1220 mgBr / 100g and a post-wash gum content of 15 mg / 100mL. The reaction was carried out over 4.0 h. -1 and 7.5h -1 After reacting at 200℃ and 3.0MPa for 80 hours, the olefin content in the reformed oil was 28mgBr / 100g, and the gum content after washing was 1.5mg / 100mL.
[0085] Example 6
[0086] (1) Weigh 47.0g of aluminum nitrate and 19.5g of zinc nitrate (Zn / Al molar ratio 0.6) and dissolve them in 500g of water. Mix them thoroughly to obtain mixed solution I.
[0087] (2) Add 8% sodium carbonate aqueous solution (containing a small amount of sodium hydroxide solution with a concentration of 0.4 mol / L) dropwise to mixed solution I, maintain the pH of the solution at 9.0, and then react at 50°C for 120 hours; then filter and wash, and dry at 80°C for 24 hours to obtain mixed metal hydroxide layered material;
[0088] (3) Then take out 10g of the mixed metal hydroxide layered material obtained in step (2), add 600g of polyvinyl alcohol solution with a molecular weight of 30,000-50,000 (the concentration of polyvinyl alcohol solution is 15%), treat at 80°C for 7 hours, then filter and wash, and dry at 90°C for 60 hours to obtain the intermediate.
[0089] (4) Take the intermediate obtained in step (3), add 5g of alumina monohydrate and 2g of guar gum powder, then knead and extrude into strips, dry at 120°C for 12 hours, and calcine at 500°C for 6 hours to obtain the first refined preparation, wherein the amount of binder added is 32% of the mass of the intermediate based on alumina.
[0090] In the first refined preparation obtained in Example 6, based on the weight of the first refined preparation, the content of ZnAl mixed metal oxide is 67.8 parts and the content of binder is 32.2 parts.
[0091] 20g of the first refined product and 10g of the second refined product (containing 80 parts of MCM-22 molecular sieve and 20 parts of alumina, with a SiO2 / Al2O3 molar ratio of 30) were evaluated. The raw material was reformed oil with an olefin content of 1220 mgBr / 100g and a post-wash gum content of 15 mg / 100mL. The reaction time was 8.0h. -1 and 4.0h -1After reacting at 220℃ and 3.0MPa for 80 hours, the olefin content in the reformed oil was 12mgBr / 100g, and the gum content after washing was 1.5mg / 100mL.
[0092] Example 7
[0093] (1) Weigh 47.0g of aluminum nitrate and 113.0g of gallium nitrate (Ga / Al molar ratio 2) and dissolve them in 500g of water. Mix them thoroughly to obtain mixed solution I.
[0094] (2) Add 5% sodium carbonate aqueous solution (containing a small amount of sodium hydroxide solution with a concentration of 0.9 mol / L) dropwise to mixed solution I, maintain the pH of the solution at 10.0, and then react at 120℃ for 24 hours; then filter and wash, and dry at 90℃ for 24 hours to obtain mixed metal hydroxide layered material;
[0095] (3) Then take out 10g of the mixed metal hydroxide layered material obtained in step (2), add 1200g of polyvinyl alcohol solution with a molecular weight of 10000-20000 (the concentration of polyvinyl alcohol solution is 9%), treat at 80°C for 7 hours, then filter and wash, and dry at 80°C for 80 hours to obtain the intermediate.
[0096] (4) Take the intermediate obtained in step (3), add 30g of alumina monohydrate and 2g of guar gum powder, then knead and extrude into strips, dry at 120°C for 12 hours, and calcine at 500°C for 6 hours to obtain the first refined preparation, wherein the amount of binder added is 60% of the mass of the intermediate based on alumina.
[0097] In the first refined preparation obtained in Example 7, based on the weight of the first refined preparation, the content of GaAl mixed metal oxide is 59.9 parts and the content of binder is 40.1 parts.
[0098] 20g of the first refining agent was mixed with 5g of the second refining agent (containing 80 parts of MCM-56 molecular sieve and 20 parts of alumina, with a SiO2 / Al2O3 molar ratio of 40) for evaluation. The raw material was reformed oil with an olefin content of 600mgBr / 100g and a post-wash gum content of 6mg / 100mL. The reaction was carried out over 8.0 hours. -1 and 2.0h -1 After reacting at 260℃ and 3.0MPa for 80 hours, the olefin content in the reformed oil was 12mgBr / 100g, and the gum content after washing was 1.0mg / 100mL.
[0099] Example 8
[0100] (1) Weigh 47.0g of aluminum nitrate and 143.8g of cerium nitrate (Ce / Al molar ratio 2) and dissolve them in 500g of water. Mix them thoroughly to obtain mixed solution I.
[0101] (2) Add 5% sodium carbonate aqueous solution (containing a small amount of potassium hydroxide solution with a concentration of 0.7 mol / L) dropwise to mixed solution I, maintain the pH of the solution at 10.0, and then react at 120℃ for 24 hours; then filter and wash, and dry at 90℃ for 24 hours to obtain mixed metal hydroxide layered material;
[0102] (3) Then take out 10g of the mixed metal hydroxide layered material obtained in step (2), add 1200g of polyvinyl alcohol solution with a molecular weight of 10000-20000 (the concentration of polyvinyl alcohol solution is 9%), treat at 80°C for 7 hours, then filter and wash, and dry at 80°C for 80 hours to obtain the intermediate.
[0103] (4) Take the intermediate obtained in step (3), add 30g of alumina monohydrate and 3g of cellulose powder, then knead and extrude the mixture, dry it at 120°C for 12 hours, and calcine it at 500°C for 6 hours to obtain the first refined product, wherein the amount of binder added is 60% of the mass of the intermediate based on alumina.
[0104] In the first refined preparation obtained in Example 8, based on the weight of the first refined preparation, the content of CeAl mixed metal oxide is 30.3 parts and the content of binder is 59.7 parts.
[0105] 20g of the first refining agent was mixed with 5g of the second refining agent (containing 40 parts of SAPO-40 molecular sieve, 40 parts of MCM-22 molecular sieve, and 20 parts of alumina; the SiO2 / Al2O3 molar ratio of SAPO-40 molecular sieve was 55, and the SiO2 / Al2O3 molar ratio of MCM-22 molecular sieve was 26) for evaluation. The raw material was reformed oil with an olefin content of 600mgBr / 100g and a post-wash gum content of 6mg / 100mL. The reaction was carried out over 8.0h. -1 and 2.0h -1 After reacting at 260℃ and 3.0MPa for 80 hours, the olefin content in the reformed oil was 12mgBr / 100g, and the gum content after washing was 1.0mg / 100mL.
[0106] Example 9
[0107] (1) Weigh out 47.0g of sodium aluminate and dissolve it in 250g of water to obtain mixed solution I. Dissolve 134.6g of tin nitrate (Sn / Al molar ratio 2) in 250g of water and then fully dissolve and mix it with mixed solution I to obtain solution II.
[0108] (2) Add 10% sodium carbonate aqueous solution dropwise to mixed solution II (which contains a small amount of sodium hydroxide solution with a concentration of 0.6 mol / L), maintain the pH of the solution at 10.5, and then react at 90°C for 24 hours; then filter and wash, and dry at 90°C for 24 hours to obtain mixed metal hydroxide layered material;
[0109] (3) Then take out 10g of the mixed metal hydroxide layered material obtained in step (2), add 700g of polyvinyl alcohol solution with a molecular weight of 50,000-80,000 (the concentration of polyvinyl alcohol solution is 12%), treat at 70°C for 20 hours, then filter and wash, and dry at 80°C for 80 hours to obtain the intermediate.
[0110] (4) Take the intermediate obtained in step (3), add 30g of alumina monohydrate and 2g of guar gum powder, then knead and extrude into strips, dry at 120°C for 12 hours, and calcine at 500°C for 6 hours to obtain the first refined preparation, wherein the amount of binder added is 40% of the mass of the intermediate based on alumina.
[0111] In the first refined preparation obtained in Example 9, based on the weight of the first refined preparation, the content of SnAl mixed metal oxide is 70.2 parts and the content of binder is 39.8 parts.
[0112] 20g of the first refining agent was mixed with 5g of the second refining agent (containing 40 parts of SAPO-40 molecular sieve, 40 parts of MCM-22 molecular sieve, and 20 parts of alumina; the SiO2 / Al2O3 molar ratio of SAPO-40 molecular sieve was 55, and the SiO2 / Al2O3 molar ratio of MCM-22 molecular sieve was 26) for evaluation. The raw material was reformed oil with an olefin content of 630mgBr / 100g and a post-wash gum content of 6mg / 100mL. The reaction was carried out over 8.0 hours. -1 and 2.0h -1 After reacting at 260℃ and 3.0MPa for 80 hours, the olefin content in the reformed oil was 12mgBr / 100g, and the gum content after washing was 1.0mg / 100mL.
[0113] Example 10
[0114] (1) Weigh 47.0g of aluminum nitrate and 85.2g of zinc nitrate (Zn / Al molar ratio 2) and dissolve them in 500g of water. Mix them thoroughly to obtain mixed solution I.
[0115] (2) A 10% sodium carbonate aqueous solution (containing a small amount of sodium hydroxide solution with a concentration of 0.4 mol / L) was added dropwise to mixed solution I, maintaining the pH of the solution at 9.5, and then reacted at 95°C for 24 hours; then filtered and washed, and dried at 100°C for 8 hours to obtain a mixed metal hydroxide layered material;
[0116] (3) Then take out 10g of the mixed metal hydroxide layered material obtained in step (2), add 600g of polyethylene glycol solution with a molecular weight of 2000-3000 (the concentration of polyethylene glycol solution is 15%), treat at 95°C for 7 hours, then filter and wash, and dry at 90°C for 15 hours to obtain the intermediate.
[0117] (4) Take the intermediate obtained in step (3), add 8g of alumina monohydrate and 2g of guar gum powder, then knead and extrude into strips, dry at 120°C for 18 hours, and calcine at 570°C for 2 hours to obtain the first refined preparation, wherein the amount of binder added is 15% of the mass of the intermediate based on alumina.
[0118] In the first refined preparation obtained in Example 10, based on the weight of the first refined preparation, the content of ZnAl mixed metal oxide is 85.2 parts and the content of binder is 14.8 parts.
[0119] Eight g of the first refining agent was taken and 24 g of the second refining agent (containing 80 parts of MCM-22 molecular sieve and 20 parts of alumina, with a SiO2 / Al2O3 molar ratio of 6) were evaluated. The raw material was aromatics from cracked gasoline, with an olefin content of 2630 mgBr / 100g and a gum content of 55 mg / 100mL after washing. The reaction was carried out over 2.0 h. -1 and 6h -1 After reacting at 210℃ and 2.0MPa for 80 hours, the olefin content in the reformed oil was 23mgBr / 100g, and the gum content after washing was 4.5mg / 100mL.
[0120] Example 11
[0121] Compared to Example 1, the difference lies in that the second refining agent was replaced with an equal mass (30g) of modified clay for evaluation. Its raw material was reformed oil with an olefin content of 1220mgBr / 100g and a post-wash gum content of 10mg / 100mL. The reaction was carried out over 2 hours. -1 and 12h -1 After reacting at 179℃ and 3.0MPa for 100 hours, the olefin content in the reformed oil was 500mgBr / 100g, and the gum content after washing was 0.8mg / 100mL.
[0122] Comparative Example 1
[0123] The difference compared to Example 1 is that the refining agent is only USY molecular sieve, containing 70 parts USY molecular sieve and 30 parts alumina. The raw material is reformed oil with an olefin content of 1220 mgBr / 100g and a washed colloidal content of 10 mg / 100mL. The reaction time is 2 hours. -1 and 12h -1After reacting at 179℃ and 3.0MPa for 100 hours, the olefin content in the reformed oil was 200mgBr / 100g, and the gum content after washing was 6mg / 100mL.
[0124] The embodiments described above are merely detailed descriptions of the technical solutions of the present invention, but the present invention is not limited to the above embodiments, that is, the present invention does not depend on the steps described in the above embodiments to be implemented. In summary, any improvements made to the present invention by those skilled in the art, including the substitution of the raw materials and additives described in the present invention, the selection of specific implementation methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for refining reformed oil, comprising: The reactants are contacted with a reforming oil refining agent to obtain refined reforming oil. The reforming oil refining agent includes a first refining agent and a second refining agent. The first refining agent includes a mixed metal oxide (MAAl) and a binder, and the second refining agent is a molecular sieve catalyst or clay. The reactants first pass through the first refining agent and then through the second refining agent. In the first refining agent, M in the mixed metal oxide (MAAl) is selected from one or more of Zn, Fe, Ga, Sn, La, and Ce. The binder is selected from at least one of alumina and silica. The molecular sieve is selected from at least one of USY, β, MCM-22, MCM-56, AlPO4-5, SAPO-5, SAPO-37, and SAPO-40 molecular sieves.
2. The refining method according to claim 1, characterized in that, The olefin content in the reaction raw materials, calculated by the bromine index, is 300~2800 mgBr / 100g, and the mass content of the washed gum is 1~60 mg / 100mL.
3. The refining method according to claim 1, characterized in that, The contact reaction conditions for the first refining agent are as follows: reaction temperature 130~350℃, reaction pressure 0.5~4.0MPa, and liquid hourly space velocity 0.5~20h⁻¹. -1 ; and / or, The contact reaction conditions for the second refining agent are: liquid hourly space velocity (LHSV) of 0.1–20 h⁻¹. -1 The reaction temperature is 120~280℃ and the reaction pressure is 0.2~5.0MPa.
4. The refining method according to claim 1, characterized in that, In the MAl mixed metal oxide, M is selected from one or more of La, Zn, and Fe; the molecule is screened from at least one of USY, β, MCM-56, MCM-22, and SAPO-40; and the clay is at least one of modified clay, activated clay, and acidic clay.
5. The refining method according to claim 1, characterized in that, In the MAl mixed metal oxide, the M / Al molar ratio is 0.5~5.0; and / or, The SiO2 / Al2O3 molar ratio of the molecular sieve is 2~60.
6. The refining method according to claim 1, characterized in that, The molecular sieve catalyst contains a binder component, the binder being selected from at least one of silica and alumina; based on the weight of the molecular sieve catalyst, the content of the binder component is 20-90 parts; and / or, In the first refining agent, based on the weight of the first refining agent, the content of MA1 mixed metal oxide is 30-95 parts; the content of binder is 5-70 parts.
7. The refining method according to claim 1, characterized in that, In the first refining agent, based on the weight of the first refining agent, the content of MA1 mixed metal oxide is 40-85 parts; the content of binder is 15-60 parts.
8. The refining method according to claim 1, characterized in that, The mass ratio of the first refining agent to the second refining agent is 0.1 to 10.
0.
9. The refining method according to claim 1, characterized in that, The preparation method of the first purified agent includes the following steps: (1) Dissolve the aluminum salt and the metal M salt in water to prepare a mixed solution I; (2) The alkali metal solution and the mixed solution I obtained in step (1) are mixed and reacted, and the pH of the solution is maintained at 9-11 to obtain a mixed metal hydroxide layered material (MAl). X (OH) Y ; (3) Add the polyol to the mixed metal hydroxide layered material obtained in step (2) for layering treatment, and dry to obtain an intermediate; (4) The intermediate obtained in step (3) is mixed with the binder precursor, kneaded and calcined to obtain the first refined preparation.
10. The refining method according to claim 9, characterized in that, The aluminum salt mentioned in step (1) is selected from one or more of aluminum nitrate, aluminum sulfate, aluminum chloride, and sodium aluminate; and / or, The metal M salt is selected from one or more of soluble nitrates, sulfates, halides, and halates.
11. The refining method according to claim 9, characterized in that, The metal M is selected from one or more of Zn, Fe, Ga, Sn, La, and Ce; and / or the M / Al molar ratio is 0.5 to 5.
0.
12. The refining method according to claim 11, characterized in that, The metal M is selected from one or more of La, Zn, and Fe.
13. The refining method according to claim 9, characterized in that, In step (2), the alkali metal solution is a carbonate and / or hydroxide, wherein the mass fraction of the solute in the alkali metal solution is 0.01%~30%; and / or, The amount of binder precursor added in step (4) is 10% to 70% of the mass of the intermediate, based on alumina or silica.
14. The refining method according to claim 9, characterized in that, The polyol mentioned in step (3) is selected from at least one of polyethylene glycol or polyvinyl alcohol; and / or, The polyethylene glycol has a molecular weight of 400-10000, and the polyvinyl alcohol has a molecular weight of less than 130,000; and / or, The binder precursor mentioned in step (4) is one or more of alumina precursor or silica precursor.
15. The refining method according to claim 14, characterized in that, The molecular weight of the polyethylene glycol is 400-8000, and the molecular weight of the polyvinyl alcohol is 10,000-80,000.
16. The refining method according to claim 9, characterized in that, The mass percentage concentration of the polyol is 0.1% to 20%; and / or, The mass ratio of the mixed metal hydroxide layered material to the polyol is 0.05~2.
0.
17. The refining method according to claim 9, characterized in that, The reaction conditions in step (2) are as follows: reaction temperature is 50~200℃, reaction time is 1~100 hours; and / or, The stratification conditions described in step (3) are as follows: temperature is 20~120℃, and time is 0.2~48 hours.
Citation Information
Patent Citations
Protective agent for catalyst for olefin removal from aromatic hydrocarbon and its uses
CN105080619A
Reformate olefin removing refining process
CN107760358A
Reformate olefin removing refining agent utilization method
CN107760362A
Method for prolonging service life of reformate molecular sieve refined catalyst
CN103184067A
Production process of high quality biodiesel
CN106221943A